CRITERION-BASED VALIDITY OF THE DEPRESSION SCALE OF LATVIAN CLINICAL PERSONALITY INVENTORY - Perepjolkina, Viktorija; Koļesņikova, Jeļena; Mārtinsone, Kristīne; Stepens, Ainārs; Rancāns, Elmārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The main aim of this study was to evaluate the criterion validity and to estimate the cut-off score of the Depression scale (DS) and short Depression scale (DSs) for a new self-report measure – Latvian Clinical Personality Inventory (LCPI). Usefulness of DS and DSs for identifying patients with major depression were analysed based on psychometric analysis of data acquired from psychiatric inpatient sample with depressive disorder (n = 37) in comparison to randomised stratified community subsample (n = 176) selected from the overall test development sample (N = 888). The present study was carried within the framework of the National Research Program (BIOMEDICINE) 2014 – 2017 (sub-project Nr.5.8.2.). It was shown that all 24 item of DS show good to excellent discrimination power. Cronbach’s alpha was 0.97 for DS and 0.95 for DSs in test development sample. For DS, the optimal cut-off score was 26 points (sensitivity 95%, specificity 91%, and positive predicted value of 69%). For DSs, the optimal cut-off was 12 points (sensitivity 92%, specificity 89%, and positive predicted value 63%). DS and DSs of LCPI is proved to have good criterion validity in detecting depression and to be a reliable and valid instrument for assessment of depression symptoms in patients with depression and in general population. Subjects scoring at least 26 on DS or 12 points on DSs constitute a target group for further diagnostic assessment in order to determine appropriate treatment.